Determine the Vital Sign Observations that can Detect Signs of Cardiopulmonary Arrest in Patients Receiving Internal Medicine Care - Muhammad Arif Khan, Rabia Maqsood, Muhammad Abdullah Ijaz, Asfa Ahmed, Rushda Bedar, Fahad Asim, Khurram Shahzad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In certain hospitals, the Medical Emergency Team (MET) has undergone development to provide prompt and efficient treatment, effectively preventing cardiac arrests. Our objective was to assess the efficiency of observational practices in identifying anomalies in vital signs before cardiac arrest and to evaluate the requirement for implementing a MET system in hospitals across Punjab. Methods: We conducted a comprehensive review of patient charts from four hospitals, specifically focusing on individuals who experienced cardiac arrest over a span of 12 months. We meticulously documented and analyzed the vital signs, symptoms, and interventions that occurred within the 12 hours leading up to the cardiac arrest, comparing them against the trigger criteria established by the Medical Emergency Team (MET). Results: Throughout the designated study period, a total of 130 patients experienced cardiac arrest while in hospitals, with 68 cases (52%) occurring on the wards. Among these patients, 34 individuals (41%) displayed abnormal vital signs that met the criteria established by the Medical Emergency Team (MET). These abnormalities were documented, on average, 3.7 hours prior to the cardiac arrest event. Notably, during this timeframe, 14 patients did not receive any form of intervention, such as supplemental oxygen or medication. Among the remaining patients, nine received intervention within 2 hours, while nine others received intervention after more than 1 hour. It is important to mention that none of the patients responded to the initial intervention. However, only one patient required subsequent re-interventions. Practical Implication: It is essential for healthcare providers in this field to be knowledgeable, skilled, and prepared to respond promptly and effectively to cardiopulmonary arrest emergencies. By staying updated on the latest guidelines and practicing interdisciplinary collaboration, healthcare teams can strive towards optimizing outcomes and ensuring the safety of their patients. Conclusion: There is a prevalent occurrence of notable physiological decline in the hours leading up to cardiac arrests within the wards of Punjab hospitals, indicating the potential value in implementing a Medical Emergency Team (MET) system. However, in order to fully capitalize on the benefits of a MET, it is crucial to enhance the practice of vital sign observation by the nursing staff. Keywords: Medical Emergency Team (MET), cardiac arrests, Internal Medicine.